2014
DOI: 10.3389/fnagi.2014.00042
|View full text |Cite
|
Sign up to set email alerts
|

Targeting multiple pathogenic mechanisms with polyphenols for the treatment of Alzheimer's disease-experimental approach and therapeutic implications

Abstract: Alzheimer's disease (AD) is the most prevalent neurodegenerative disease of aging and currently has no cure. Its onset and progression are influenced by multiple factors. There is growing consensus that successful treatment will rely on simultaneously targeting multiple pathological features of AD. Polyphenol compounds have many proven health benefits. In this study, we tested the hypothesis that combining three polyphenolic preparations (grape seed extract, resveratrol, and Concord grape juice extract), with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(82 citation statements)
references
References 50 publications
2
80
0
Order By: Relevance
“…No formal assessment has been made in relation to changes in sphingolipid levels in neurons after treatment with resveratrol. Nevertheless, neuroprotection has been consistently observed at <50 µM of resveratrol, which is lower than the concentration required to inhibit SK1 activity (K i = 160 ± 40 μM) and to induce apoptosis (Capiralla et al 2012;Chen et al 2005;Feng et al 2013;Lim et al 2012a;Marambaud et al 2005;Wang et al 2014). Therefore, low micromolar concentrations of resveratrol might mediate protection via a mechanism that does not involve changes in sphingolipid levels.…”
Section: Neurodegenerative Diseasementioning
confidence: 92%
“…No formal assessment has been made in relation to changes in sphingolipid levels in neurons after treatment with resveratrol. Nevertheless, neuroprotection has been consistently observed at <50 µM of resveratrol, which is lower than the concentration required to inhibit SK1 activity (K i = 160 ± 40 μM) and to induce apoptosis (Capiralla et al 2012;Chen et al 2005;Feng et al 2013;Lim et al 2012a;Marambaud et al 2005;Wang et al 2014). Therefore, low micromolar concentrations of resveratrol might mediate protection via a mechanism that does not involve changes in sphingolipid levels.…”
Section: Neurodegenerative Diseasementioning
confidence: 92%
“…In animals, oral administration of a grape-seed polyphenol extract containing resveratrol significantly attenuates the development of tau neuropathology in a mouse model of AD [185]. Treatment with a standardized grape polyphenol preparation containing resveratrol leads to the improvement of cognitive function and greatly reduces total amyloid content in the brain of J20 AD mice, an animal model of A␤ pathology [186]. According to a recent report, chronic resveratrol administration leads to decreases in the ratio of soluble A␤42/A␤40 (−42%) and in the concentration of insoluble human tau (−93%) in the parietotemporal cortex of 18-month-old mice in a triple-transgenic model of AD [187].…”
Section: Therapeutic Potential In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Other genetic variations identified by genome-wide association studies have been found to influence the risk of developing AD through their interaction with protein degradation and transport, immune activity, lipid transport and metabolism, and mitochondrial function (Tosto and Reitz 2013). Their influence upon rate of progression of AD is now beginning to be explored (Wang et al 2014). …”
Section: Individual Rates Of Declinementioning
confidence: 99%